Profile of Shingles Patients in Outpatient Settings Dermatology and Venereology - Noviani, Laura; Kariosentono, Harijono; Yasmin, Aulia; Kusumasari, Nila (Journal La Medihealtico, 2024)
Herpes zoster (HZ) is a latent varicella zoster virus (VZV) reactivation has been related to aging and immunocompromised condition that affects the skin and mucosa. It becomes increasingly common. However, studies on the clinical profile of HZ in Indonesia are still lacking. Objective of the study is to describe clinico-epidemiological profiles of HZ in Dr. Moewardi General Hospital Surakarta, Indonesia in the period of January 2018 – December 2022. We conducted a retrospective study using the medical records of patients visiting Dermatovenereology Outpatient Clinic of Dr. Moewardi General Hospital Surakarta from January 2018 to December 2022. 48 subjects included in this study 31 of them are females (65%). The subjects were dominated by those aged >50 years old (n:30; 63%). Herpes zoster mostly occurred at thoracal dermatome (n:22: 46%). Top three comorbidities were hypertension (n:10; 21%) followed by autoimmune diseases (n:9: 18%) and malignancy history (n; 6; 13%). Antiviral drugs (n:33; 69%) and antibiotic ointment (n:33; 69%) were the most therapy. More than 50% of subjects received anticonvulsant gabapentin (n:28; 58%) and one-fourth of subjects received analgesic (n:12; 25%). Herpes Zoster most affects middle adulthood population invo involving thoracal dermatome. Hypertension, autoimmune disease and history of malignancy are the common comorbidity. The main therapy of HZ is antivirus in combination with anticonvulsant and analgesic.